Mobile Stock Information System Using the Waterfall Method: Case Study at An Electronics Retailer in Bandung - Andriano, Depry; Rosadi, Dadi; Supriatna, Haris (LPPM STMIK Mardira Indonesia, 2023)
Efficient inventory control is a crucial aspect of the retail sector, particularly in the electronics industry, such as mobile phones. This study aims to assess the efficacy of the Waterfall methodology in developing a mobile stock management system that is both efficient and dependable. This study employs a qualitative methodology, gathering data from multiple mobile phone retail shops that have adopted the Waterfall method for developing a stock management system. The collected data encompasses the progression through development stages, encountered restrictions, time duration, and attained outcomes. The data is studied to ascertain the strengths and shortcomings of the Waterfall technique in the specific context of controlling cellphone stock. The research findings demonstrate that the Waterfall technique offers a well-defined framework for creating a stock management system. Delineated phases, such as requirements analysis, design, implementation, testing, and implementation, aid firms in effectively overseeing projects with a disciplined and quantifiable approach. Furthermore, the Waterfall technique enables firms to gain a comprehensive perspective of the project from initiation to completion. Nevertheless, this study also pinpointed certain shortcomings in implementing the Waterfall technique. One drawback is the need for adaptability in handling evolving requirements or enhancements that may emerge during the development process. Hence, companies must meticulously evaluate the worthiness of accommodating these alterations. Based on this study, it is determined that the Waterfall technique can be a very efficient strategy for developing a mobile phone stock management system, mainly when the specific objectives and requirements have been adequately established. However, companies must consider the possibility of evolving requirements and be open to modifying the development process as necessary. This research offers valuable insights to firms in selecting a development approach that aligns with their specific context and business requirements